PENGARUH MODEL PEMBELAJARAN PROJECT-BASED BLENDED LEARNING DENGAN MENGGUNAKAN GEO-AUGMENTED REALITY TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS X DI SMA PEMBANGUNAN LABORATORIUM UNP - firma maulidna; Ernawati Ernawati (JURNAL BUANA, 2023)
This study aims to determine the Influence of Project-Based Blended Learning Models Using Geo-Augmented Reality on Geography Learning Outcomes of Class X Students at SMA Pembangunan Laboratorium UNP. The research method used is quasi experiment with a quantitative approach. The population in this study was all class X IIS students at SMA Pembangunan Laboratorium UNP which amounted to 121 students. The sampling technique used in this study was Purposive Sampling, which was 60 students from class X IIS 1 and X IIS 3. Data collection techniques through observation, tests and documentation. The data analysis technique is an independent sample t-test (t-test) technique. Based on the results of the study, it was concluded that the influence of the Project-Based Blended Learning learning model using Geo-Augmented Reality on Basic Competence 3.7 (Hydrosphere Dynamics) is better than conventional learning models. With a value of Sig. (2- tailed) of 0.000 which is less than 0.05, so it can be decided that Ho is rejected and Ha is accepted.